Physical activity, screen time, and sleep duration of adolescents before and during COVID-19 - Moura, Ana Regina Leão Ibiapina; Moura, Maycom do Nascimento; Cabral, Patrícia Uchôa Leitão; Carvalho, Ferdinando Oliveira; Moraes, José Fernando Vila Nova de (O Mundo da Saúde, 2023)
The social isolation associated with the COVID-19 pandemic, including school closures, directly impacted the daily habits of adolescents. Thus, the present study aimed to analyze the level of physical activity, screen time, and sleep duration of adolescents before and during COVID-19. Therefore, a cross-sectional, quantitative study was carried out with 85 adolescents aged 14 to 18 years, students at a Federal Institute. Participants answered questionnaires on sociodemographic data, physical activity level, screen time, and sleep duration. Data were analyzed using the paired Student’s T-Test. The significance level adopted was p<0.05. The results revealed that there was a significant increase in sleep duration on weekdays for girls (p=0.001) and boys (p=0.001) and in screen time during the pandemic for girls (p=0.028) and boys (p= 0.004). There was a decrease in the level of physical activity of girls (p=0.025). It is concluded that, among the students at this Federal Institute, the COVID-19 pandemic increased the sleep duration and screen time of male and female adolescents and decreased the level of physical activity of girls.